Endometriosis classification systems: an international survey to map current knowledge and uptake. Issue 1 (1st March 2022) - ,; Zondervan, Krina T; Missmer, Stacey; Abrao, Mauricio S; Einarsson, Jon I; Horne, Andrew W; Johnson, Neil P; Lee, Ted T M; Petrozza, John; Tomassetti, Carla; Vermeulen, Nathalie; Grimbizis, Grigoris; et al.
Abstract: STUDY QUESTION: Which classification system for endometriosis do clinicians use most frequently, and why? SUMMARY ANSWER: Even with a high uptake of the three existing endometriosis classification systems, most clinicians managing endometriosis would like a new simple surgical descriptive system for endometriosis. WHAT IS KNOWN ALREADY: In the field of endometriosis, several classifications, staging and reporting systems have been developed and published, but there are no data on the uptake of these systems in clinical practice. STUDY DESIGN, SIZE, DURATION: A survey was designed using the online SurveyMonkey tool consisting of 11 questions concerning three domains—participants background, existing classification systems and intentions with regards to a new classification system for endometriosis. Replies were collected between 15 May and 1 July 2020. PARTICIPANTS/MATERIALS, SETTING, METHODS: A cross-sectional study was performed to gather data on the current use of endometriosis classification systems, problems encountered and interest in a new simple surgical descriptive system for endometriosis. The particular focus was on the three systems most commonly used: the Revised American Society for Reproductive Medicine (rASRM) classification, the endometriosis fertility index (EFI), and the ENZIAN classification. Data were analysed to detect statistically significant differences among user groups. MAIN RESULTS AND THE ROLE OF CHANCE: The final dataset included the replies of 1178 clinicians, including surgeons, gynaecologists, reproductive endocrinologists, fertility specialists and sonographers, all managing women with endometriosis in their clinical practice. Overall, 75.5% of the professionals indicate that they currently use a classification system for endometriosis. The rASRM classification system was the best known and used system, while the EFI system and ENZIAN system were known by a majority of the professionals but used by only a minority. The lack of clinical relevance was most often selected as a problem with using any system. The vast majority of respondents replied positively to the question on whether they would use a simple surgical descriptive system available for endometriosis, if available. LIMITATIONS, REASONS FOR CAUTION: While the total number of respondents was acceptable, some regions/professions were not sufficiently represented to draw conclusions. WIDER IMPLICATIONS OF THE FINDINGS: The findings of the survey suggest that clinicians worldwide are open to using a new classification system for endometriosis that can achieve standardized reporting and is clinically relevant and simple. The findings therefore support future initiatives for the development of a new descriptive system for endometriosis and provide information on user expectations and conditions for universal uptake of such a system. STUDY FUNDING/COMPETING INTEREST(S): The meetings and activities of the working group were funded by the American Association of Gynecologic Laparoscopists, European Society for Gynecological Endoscopy, ESHRE and World Endometriosis Society. A.W.H. reports grant funding from the MRC, NIHR, CSO, Roche Diagnostics, Astra Zeneca, Ferring, Charles Wolfson Charitable Trust, Standard Life, and consultancy fees from Roche Diagnostics, AbbVie, Nordic Pharma and Ferring, outside the submitted work. In addition, A.W.H. has a patent Serum biomarker for endometriosis pending. He is Chair of TSC for STOP-OHSS and CERM trials and Chair of RCOG Academic Board 2018–2021. M.A. reports being member of the executive board and vice president of AAGL. N.P.J. reports personal fees from Abbott, Guerbet, Myovant Sciences, Vifor Pharma, Roche Diagnostics outside the submitted work; he is also President of the World Endometriosis Society and chair of the trust board. S.M. reports grants from AbbVie, DoD, NIH and Marriot Family Foundation, honoraria from University British Columbia and WERF, support for speaking at conferences (ESHRE, CanSAGE, Endometriosis UK, UEARS, IFFS, IASP, National Endometriosis Network UK) participation on Advisory Boards from AbbVie and Roche, outside the submitted work. She also discloses having a leadership or fiduciary role in SWHR, WERF, WES, ASRM and ESHRE. C.T. reports grants, consulting and speakers' fees non-financial support and other from Merck SA, non-financial support and other consulting fees from Gedeon Richter and Nordic Pharma, and support for meeting attendance non-financial support from Ferring Pharmaceuticals, outside the submitted work and without private revenue. K.T.Z. reports grants from Bayer Healthcare, MDNA Life Sciences, Volition Rx, and Evotec (Lab282—Partnership programme with Oxford University), non-financial support from AbbVie Ltd, all outside the submitted work; and is a Board member (Secretary) of the World Endometriosis Society and World Endometriosis Research Foundation. J.P. reports personal fees from Hologic, Inc., outside the submitted work; he is also a member of the executive boards of ASRM and SRS. The other authors had nothing to disclose.